Neuroimaging Findings in Tuberculosis: A Single‐Center Experience in 559 Cases. Issue 5 (21st May 2019) - Azeemuddin, Muhammad; Alvi, Amna; Sayani, Raza; Khan, Misha Khalid; Farooq, Salman; Beg, M. Asim; Awan, Safia; Wasay, Mohammad
ABSTRACT: BACKGROUND AND PURPOSE: There is a paucity of literature related to the neuroimaging of CNS tuberculosis (TB) and largely covers pediatric CNS TB. The objective of this study was to determine the frequency of different forms of CNS TB and its associated complications and to study longitudinal disease course using computed tomography (CT) and MRI. METHODS: Retrospective chart and imaging review of patients diagnosed with CNS TB in a tertiary care hospital in Pakistan over a 10‐year period. A total of 452 initial brain MRI and 209 CT scans were reviewed by an expert radiologist specialized in neuroimaging. This was followed by review of 53 MRI/52 CT and 7 MRI/14 CT first and second follow‐up scans, respectively. RESULTS: Note that 559 patients, 296 males and 263 females were included in the study. On the initial CT scans, tuberculomas were found in 25 (12%), infarction in 54 (25%), basal meningeal enhancement in 29 (14%), and hydrocephalus in 84 (40%). On initial MRI, tuberculomas were found in 182 (40%), infarction in 120 (27%), basal meningeal enhancement in 184 (41%), and hydrocephalus in 116 (26%). On review of follow‐up CT scans, 13 (25%) showed new or worsening hydrocephalus, 8 (15%) showed new infarcts, 1 exhibited new tuberculoma, and 5 showed worsening cerebral edema. On review of follow‐up MRI scans, new or worsening hydrocephalus was seen in 3 (6%), new infarcts in 3 (6%), new tuberculoma in 10 (19%), worsening cerebral edema in 7 (13%), and TB myelitis in 4 (8%) patients. CONCLUSIONS: Tuberculoma, hydrocephalus, and cerebral infarcts are the most prominent findings in CNS tuberculosis. Our study showed development of new lesions on subsequent neuroimaging suggesting a dynamic and progressive nature of the disease process in some individuals.